For the greater good? Questioning the social licence of extractive-led development in Western Australia's Martuwarra Fitzroy River region. Issue 3 (September 2021) - Poelina, Anne; Brueckner, Martin; McDuffie, Magali
Highlights: The paper maps the history of colonialism and dispossession in Western Australia's Kimberley region. Contemporary resource extraction is shown to be an extension of colonial, orthodox development. Water extraction proposals are shown to fail to meet the public interest from an Indigenous vantage point Proposed developments risk the creation of adverse socio-cultural and ecological mining legacies. Decolonising development alternatives are proposed for development on just terms. Abstract: Economic development in Australia, especially resource development, has purportedly long been pursued for the greater good of the nation and its people and is thus often equated to moral progress. Yet, despite the celebrated spoils of the resources sector, Indigenous Australians have persistently been denied the benefits of economic progress owing to a history of colonialism, dispossession, segregation and assimilation policies, which have contributed to the marginalisation of Indigenous people to the present day. Thus, this article asks whether orthodox resource-led development has a social licence, and importantly for whose greater good? This paper applies a social licence lens to current water extraction proposals for Western Australia's remote Martuwarra Fitzroy River region where ecological values have largely remained intact and Indigenous people make up over 60 per cent of the population. It is argued the proposed water extraction plans hold little promise of serving either local or national interests when judged holistically and risk perpetuating adverse socio-cultural and ecological legacies from extractive activities for local Indigenous peoples. Within the Martuwarra Fitzroy River context, this paper seeks to redefine the 'greater good' and to articulate 'socially licenced' development alternatives without the ecological and cultural trade-offs typical of orthodox development.